Determining the water quality of Lake Delice (İmranli-Sivas). - Mutlu, Ekrem; Yani̇k, Telat; Akca, İbrahim; Kutlu, Banu; Sonmez, Adem Yavuz (Adem Yavuz Sönmez, 2015)
The objectives of this study were to observe the monthly and annual changes in water samples through physico-chemical methods, to determine the water quality properties, to reveal the pollution problems, to determine the suitability level in terms of aquatic life, and to classify the quality of water in accordance with the ISWC criteria. This study has been carried out through monthly sampling during April 2011-March 2014 in 3 stations at Lake Delice. The samples have been immediately taken to the laboratories for analyses. 1st station is at the Western side of the lake (roadside), 2nd point is at entrance point of Brook Araba into the lake (northwestern side of the lake), and the 3rd station is located at Southwestern side of the lake (the deepest point). It has been determined that the lake is suitable for aquaculture of cold water fish in winter and spring months and for warm-water fish in summer and autumn months. Furthermore, the pollution of this water resource should be prevented, and the water quality protection provisions required for sustaining and improving the ecological balance constituted by the natural fish stocks and other aquatic creatures should be made immediately, and this lake should be monitored continuously.
Keywords: Naval Science; hafik; V; Naval architecture. Shipbuilding. Marine engineering; Aquaculture. Fisheries. Angling; SH1-691; VM1-989; lake delice; sivas; water quality; Sivas; Hafik; Water quality; Lake Delice